Implementation of Dewey’s and Prosser’s Philosophy on Vocational Education in Indonesia - Muchlas, Muchlas; Triatmaja, Adhy Kurnia (Universitas Ahmad Dahlan, 2025)
This study aims to explore the implementation of the philosophical values of two influential figures, Dewey and Prosser, in the organization of vocational education in Indonesia. The research subjects consisted of 86 vocational school principals from Java Island, selected through purposive sampling. Data were collected using a questionnaire with a Likert Scale to assess the respondents' perceptions of the indicators of philosophical values implemented in schools. The data were analyzed using a quantitative method to present the underlying meanings and values of vocational education practices from the perspective of the two philosophers. The study's findings indicate that vocational education in Indonesia has incorporated many of Dewey's pragmatic philosophical values. However, its implementation has not yet been effective, particularly in relation to the values associated with the principles of learning by doing and experience-based skills. Similarly, the values of Prosser's philosophy, which emphasize the relationship between theory and practice, face challenges due to limited funding and a lack of investment in practical tools that meet industry standards. Nevertheless, vocational education holds significant potential for development if stakeholders can bridge the gap between theory and practice in the industrial world.